Purification and characterization of a novel plantaricin, KL-1Y, from Lactobacillus plantarum KL-1 - Rumjuankiat, Kittaporn; Perez, Rodney Horanda; Pilasombut, Komkhae; Keawsompong, Suttipun; Zendo, Takeshi; Sonomoto, Kenji; Nitisinprasert, Sunee (My University, 2015)
Three bacteriocins from Lactobacillus plantarum KL-1 were successfully purified using ammonium sulfate precipitation, cation-exchange chromatography and reverse-phase HPLC. The bacteriocin peptides KL-1X, -1Y and -1Z had molecular masses of 3053.82, 3498.16 and 3533.16 Da, respectively. All three peptides were stable at pH 2–12 and 25 °C and at high temperatures of 80 and 100 °C for 30 min and 121 °C for 15 min. However, they differed in their susceptibility to proteolytic enzymes and their inhibition spectra. KL-1Y showed broad inhibitory activities against Gram-positive and Gram-negative bacteria, including Salmonella enterica serovar Enteritidis DMST 17368, Pseudomonas aeruginosa ATCC 15442, P. aeruginosa ATCC 9027, Escherichia coli O157:H7 and E. coli ATCC 8739. KL-1X and -1Z inhibited only Gram-positive bacteria. KL-1X, KL-1Y and KL-1Z exhibited synergistic activity. The successful amino acid sequencing of KL-1Y had a hydrophobicity of approximately 30 % and no cysteine residues suggested its novelty, and it was designated “plantaricin KL-1Y”. Plantaricin KL-1Y exhibited bactericidal activity against Bacillus cereus JCM 2152T. Compared to nisin, KL-1Y displayed broad inhibitory activities of 200, 800, 1600, 800, 400 and 400 AU/mL against the growth of Bacillus coagulans JCM 2257T, B. cereus JCM 2152T, Listeria innocua ATCC 33090T, Staphylococcus aureus TISTR 118, E. coli O157:H7 and E. coli ATCC 8739, respectively, whereas nisin had similar activities against only B. coagulans JCM 2257T and B. cereus JCM 2152T. Therefore, the novel plantaricin KL-1Y is a promising antimicrobial substance for food safety uses in the future.
Keywords: Bactericidal activity; Bacteriocin; Characterization; Lactobacillus plantarum; Purification; Synergism